Hadith #6184 - Sahih al-Bukhari - 'Utban bin Malik Al-Ansari (Sahih al-Bukhari)
who was one of the men of the tribe of Bani Salim: Allah’s Messenger (ﷺ) came to me and said, “If anybody comes on the Day of Resurrection who has said: La ilaha illal-lah, sincerely, with the intention to win Allah’s Pleasure, Allah will make the Hell-Fire forbidden for him.”
Grade: Sahih